FRI0328 Efficacy and safety of tocilizumab (TCZ) in patients with systemic juvenile idiopathic arthritis (SJIA): 2-year data from tender, a phase 3 clinical trial. (23rd January 2014) - De Benedetti, F.; Brunner, H.; Ruperto, N.; Kenwright, A.; Devlin, C.; Calvo, I.; Cuttica, R.; Ravelli, A.; Schneider, R.; Eleftheriou, D.; Wouters, C.; Xavier, R.; et al.
Abstract : Background: The IL-6 receptor inhibitor TCZ was investigated for the treatment of sJIA patients (pts) in the ongoing 3-part, 5-y, phase 3 TENDER study. Objectives: Long-term efficacy and safety are presented. Methods: 112 pts 2-17 y with active sJIA for ≥6 mo were randomised 2:1 to TCZ (8 mg/kg if body weight ≥30 kg; 12 mg/kg if <30 kg, n=75) or placebo (n=37) every 2 wks for 12 wks in part 1; all pts received open-label TCZ in part 2 (to 104 wks). Oral corticosteroid (CS) tapering was permitted according to pre-defined criteria. Data were cut for each ongoing pt 104 wks from randomisation, with first dose of TCZ as baseline (BL) in the extension. At the data cut, 61 pts received ≥104 wks of TCZ, 32 pts were ongoing and 20 withdrew, including 1 at wk 104 (safety, 9; insufficient therapeutic response, 5; other non-safety, 6). Results: BL characteristics included mean disease duration of 5.2 y, mean active joint count of 19.8 and presence of fever in 43% of pts. At 2 y, 88% and 71% of pts on TCZ achieved JIA ACR70 and 90 responses (Table 1 ). In pts on oral CS at BL, 60% stopped by wk 104, and mean dose decreased from 0.30 mg/kg/d at BL to 0.04 at wk 104. 47 serious adverse events (SAEs), 15 considered TCZ-related, occurred in 35 pts (Table 2 ). Of 22 serious infections (8 considered TCZ-related) in 20 pts, all but 1 resolved (pt death). 3 pts died (1, suspected tension pneumothorax; 1 traffic accident [both unrelated]; 1 suspected streptococcal sepsis; possibly related]). 3 additional pts died 6, 12 and 13 mos after leaving the study. Conclusions: TENDER 2-y results demonstrated continued maintenance of efficacy and no change in the safety profile with long-term TCZ treatment. Disclosure of Interest: F. De Benedetti Grant/Research support from: Abbott, BMS, Pfizer, SOBI, Novimmune, Roche, Novartis, Consultant for: BMS, Pfizer, Roche, H. Brunner Consultant for: Genentech, Novartis, UCB, Jansen, Medimmune, GSK, BMS, PFizer, Employee of: Cincinnati Children's Hospital Medical Center, N. Ruperto Grant/Research support from: Abbott, Astrazeneca, BMS, Centocor Research and Development, Eli Lilly and Company, "Francesco Angelini" s.p.a., GSK, Italfarmaco, Merk Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers Bureau: Astrazeneca, BMS, Jansen Biologics BV, Novartis, Roche, A. Kenwright Employee of: Roche, C. Devlin Shareholder of: Roche, Employee of: Roche, I. Calvo: None Declared, R. Cuttica Grant/Research support from: Novartis, Hoffmann-La Roche, Consultant for: Hoffmann-La Roche, Speakers Bureau: Hoffmann-La Roche, A. Ravelli: None Declared, R. Schneider: None Declared, D. Eleftheriou: None Declared, C. Wouters: None Declared, R. Xavier Consultant for: Pfizer, Roche, Speakers Bureau: Pfizer, Roche, Abbott, L. Zemel: None Declared, E. Baildam: None Declared, R. Burgos-Vargas Grant/Research support from: Abbott, Consultant for: Abbott, BMS, Jannsen, Pfizer, Roche, Speakers Bureau: Abbott, BMS, Jannsen, Pfizer, Roche, P. Dolezalova Grant/Research support from: Novatis, Speakers Bureau: BMS, Novartis, S. M. Garay: None Declared, R. Joos: None Declared, A. Grom Consultant for: Novartis, Merck, N. Wulffraat: None Declared, Z. Zuber: None Declared, F. Zulian: None Declared, D. Lovell Grant/Research support from: BMS, Abbott, Consultant for: Astrazeneca, Wyeth, Amgen, Pfizer, Regeneron, Roche, Novartis, UMC, Xoma, A. Martini Grant/Research support from: Abbott, Astrazeneca, BMS, Centocor Research and Development, Eli Lilly and Company, "Francesco Angelini" s.p.a., GSK, Italfarmaco, Merk Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers Bureau: Astrazeneca, Novartis, BMS, GSK